2021
DOI: 10.3390/universe7050117
|View full text |Cite
|
Sign up to set email alerts
|

Quantum State Evolution in an Environment of Cosmological Perturbations

Abstract: We study the pure and thermal states of quantized scalar and tensor perturbations in various epochs of Universe evolution. We calculate the density matrix of non-relativistic particles in an environment of these perturbations. We show that particle’s motion can be described by a stochastic equation with a noise coming from the cosmological environment. We investigate the squeezing of Gaussian wave packets in different epochs and its impact on the noise of quantized cosmological perturbations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…( 21) the noise term (its correlation functions) depend on the quantum state of the graviton. We have discussed the evolution of Gaussian wave packets in various epochs in [45]. We concluded that the squeezing described by small i(Γ e − Γ * e ) remains small (≃ k 3 ) during the radiation and baryonic eras.…”
Section: The Noise From the Squeezed States Of (Inflationary) Gravitonsmentioning
confidence: 93%
“…( 21) the noise term (its correlation functions) depend on the quantum state of the graviton. We have discussed the evolution of Gaussian wave packets in various epochs in [45]. We concluded that the squeezing described by small i(Γ e − Γ * e ) remains small (≃ k 3 ) during the radiation and baryonic eras.…”
Section: The Noise From the Squeezed States Of (Inflationary) Gravitonsmentioning
confidence: 93%
“…While the direct detectability of stochastic background of primordial gravitational waves has been questioned [20], recently there are studies on their potential detectability via quantum noise. Quantum mechanical treatment of gravitational field is shown to be able to induce fluctuations or noise in the lengths of the arms of gravitational wave detectors where the characteristics of the noise depend on the quantum state of the gravitational field and while such noise is very small for coherent states, it can be greatly enhanced especially in squeezed states by an exponential of the squeezing parameter and hence, potentially detectable [21][22][23][24][25]. Therefore, it is interesting to study the stochastic signals of the inflationary gravitational waves in wake of these recent developments.…”
Section: Introductionmentioning
confidence: 99%